Plant Ecophysiolomics to face the challenges of global change - Enrique Ostria-Gallardo; Luisa Bascuñán-Godoy (Global Journal of Ecology - Peertechz Publications, 2021)
As consequence of global change, there has been an intensification of syndromes such as land desertification in several regions of the world. Plant functioning is threatened by this scenario. Given its importance for sustaining mostly all terrestrial life, a renewed interest has risen in studying the effects of global change over plant functioning, particularly for its role in ecosystem energy fluxes, and as the basis for food, fiber, biofuels and other products used by humans. This mini review attempts to draw attention on the benefits of study the effects of global change over plant functioning under a comprehensive approach. Ecophysiolomics, the merge of Plant Physiology, Ecophysiology and Omics, is an emerging field helping to elucidate the mechanisms, from molecular to population and community levels, underlying plant growth and development, against the effects of global change. By integrating and merging different approaches such as Ecophysiolomics, we will maximize not only our understanding of plant-to-ecosystem resilience, but also, the support and advice for policy makers and governments to better manage the threats and challenges of global change.